Chemically and temporally resolved oxidative potential of urban fine particulate matter. (15th December 2021) - Hsiao, Ta-Chih; Chou, Li-Ti; Pan, Shih-Yu; Young, Li-Hao; Chi, Kai-Hsien; Chen, Albert Y.
Abstract: Vehicle emissions are an important source of particulate matter (PM) in urban areas and have well-known adverse health effects on human health. Oxidative potential (OP) is used as a quantification metric for indexing PM toxicity. In this study, by using a liquid spot sampler (LSS) and the dithiothreitol (DTT) assay, the diurnal OP variation was assessed at a ground-level urban monitoring station. Besides, since the monitoring station was adjacent to the main road, the correlation between OP and traffic volume was also evaluated. PM components, including metals, water-soluble inorganic aerosols (WSIAs), black carbon (BC), and polycyclic aromatic hydrocarbons (PAHs), were also simultaneously monitored. The daytime and evening mean ± std volume-normalized OP (OPv) were 0.46 ± 0.27 and 0.48 ± 0.26 nmol/min/m 3, and exhibited good correlations with PM1.0 and BC; however, these concentrations were only weakly correlated with mass-normalized OP (OPm). The mean ± std OPm was higher in the daytime (41.3 ± 13.8 pmol/min/μg) than in the evening (36.1 ± 11.5 pmol/min/μg). According to the PMF analysis, traffic emissions dominated the diurnal OP contribution. Organic matter and individual metals associated with non-exhaust traffic emissions, such as Mn, Fe, and Cu, contributed substantially to OP. Diurnal variations of PAH concentrations suggest that photochemical reactions could enhance OP, highlighting the importance of atmospheric aging on PM toxicity.